Web-based salary system for palm oil estate farmer / Azahari Abdul Aziz - Azahari, Abdul Aziz (2005)
This Salary System is basically the system that is built to manage the salary at a Felda. This system allows user to view, add, delete and update information about their salary. The target users for this system are palm oil estate farmers, staff and manager. Every user has different roles in this system. Palm oil estate farmers only can view their salary system. Meanwhile, stafife only use it to key in data and view fanners' statistical salary analysis. Manager or administrator has the power to change anything about the data in the system. This system is focusing on the salary system for Felda Kemasul. This system is built as a web-based system that can be access online. This system is developed based on human computer interactiorL "PHP: Hypertext Preprocessor" as the programming language, MySQL is selected as the database and Apache as the web server. This system provides updating of information and retrieving of data and in an efficient manner and less time consuming. This system is hopefully can manage the flow of salary smoothly.